A importância da literatura infantil para a luta antirracista: análise das obras Amoras (2018), de Emicida, O pequenо príncipe preto (2020), de Rodrigo França e Com qual penteado eu vou? (2021), de Kiusam de Oliveira - Santos, Beatriz Montes dos (2025)
This research aims to highlight the importance of children's literature for the anti-racist struggle through the analysis of the works Amoras (2018), by Emicida, O pequeno príncipe preto (2020), by Rodrigo França, and Com qual penteado eu vou? (2021), by Kiusam de Oliveira. The problem of this work was shaped by the observation that many children's literary narratives are portrayed from a Eurocentric and colonial point of view, which does not welcome identity diversity and excludes historically marginalized groups, such as black people. In view of this, we analyzed the aforementioned books with the purpose of identifying the ethnic-racial and cultural aspects related to black people. Next, we discuss the importance of positive black representations in children's literature; we investigate the motivations related to the writing of the authors of the analyzed books to infer the relevance of their trajectories for their productions in the field of children's literature. Finally, we address the obstacles present in children's schooling processes and reflect on the importance of including anti-racist resources and practices in educational institutions. We conclude that children's works with plots in which black people are represented from perspectives contrary to subalternity are essential tools for the anti-racist struggle, since they embrace diversity and contribute to children's development, thus enabling the construction of a more just and less prejudiced society. As theoretical support, we brought the contributions of Regina Zilberman and Marisa Lajolo (1988; 2006), to understand the aspects of children's literature; Munanga (2004) for the definitions of race and racism; Neusa Santos (1983) and Cida Bento (2022), to address the concepts of blackness and whiteness; Bárbara Carine (2023), to discuss anti-racist practices in schools, among others.